Implementation of GMSK Modulation Using GNU Radio for Cube Satellite - De Shepherd Guella Winisia Zega; Dananjaya Ariateja; Herwin Hutapea (International Journal of Enterprise Modelling, 2026)
The CubeSat platform has evolved to support a wide range of space missions, modulation schemes, and frequency bands, leading to a need for dependable ground-to-satellite communication systems. Software-defined radio (SDR) has become the modern RF communication system chosen method. The goal of this research is to be able to communicate with a satellite using a configurable SDR and GNU Radio. Other research has conducted GMSK signal simulations, SDR-to-SDR testing, or receiver-side validation only, while this study evaluates GMSK modulation using a CubeSat Engineering Model (EM). Signal was conducted with 276-byte data packets. Unpadded SDR transmissions failed to communicate, whereas a conventional RF signal generator achieved 100% success. Review of the RF generator revealed that it produces 1000 transmission symbols by default, including the data packet. Considering the longer transmission symbols, extra null symbols (zero-padding) were added to the end of the SDR packet in increments of 5 to 50 bytes. Symbol adjustment attempt led to a 100% packet-rate success of the GMSK communication link between the SDR and the EM. Findings revealed that consideration of signal factors such as transmission length, flowgraph configurations, and hardware compatibility is critical for communication performance.